Antileishmanial activities of 2,4-diaminoquinazoline putative dihydrofolate reductase inhibitors. - Berman, J D (1989)
2,4-Diaminoquinazoline analogs of folate were assessed as antileishmanial agents and as dihydrofolate reductase inhibitors. Against Leishmania major in human macrophages in vitro, two compounds with tertiary amines attached directly to the quinazoline ring were remarkably active. The 50% effective doses were in the picogram per milliliter range (12 to 91 pg/ml), and the in vitro therapeutic indices were approximately 10(5). These compounds were 1,000 times more active on an absolute basis and had a 100 times more favorable therapeutic index than any compound previously tested in this model. Antileishmanial activity was not correlated with activity against Leishmania mexicana promastigote reductase, which suggests that folate utilization in general, rather than reductase activity specifically, was being inhibited.